[OP.3B.07] MULTIDISCIPLINARY TREATMENT FOR THE VERY ELDERLY HYPERTENSIVE PATIENT. (September 2016) - Jardim, T.; Jardim, L.; Sousa, A.; Barroso, W.; Pimenta, C.; Jardim, P.
Abstract : Objective: World population is getting older. Patients with more than 80 years old, referred as very elderly are more common each day. Few studies with this complex population studied a multidisciplinar hypertension treatment approach. The objective of this study was to evaluate the effect of a multidisciplinar treatment in very elderly hypertensive patients from a specialized service. Design and method: Observational retrospective study of patients with a regular follow up (least two visits on the last 12 months) at the Hypertension League from the Federal University of Goias – Brazil, a multidisciplinary specialized centre in the treatment of hypertensive patients. Patients with 80 years old or more on june 2014 were included. Data from their first (V1) and last visit to the service (Vf) were collected and compared. Blood pressure (BP), number of antihypertensive drugs, class of antihypertensive medication and rate of blood pressure control (BP <  = 140 x 90 mmHg) were analised. Statistical analysis performed with software SPSSR version 20.0. Values of p < 0, 05 were considered significant. Results: The median follow up time of the 71 included patients was 15, 22 years and 26, 8% of them were men. Mean age of the group was 69, 2 years in V1 and 84, 53 in Vf. Figure. No caption available. Conclusions: Multidisciplinary approach in hypertension treatment for very elderly patients reduced blood pressure and increased control rate, with and optimization of the antihypertensive drugs prescription.